LAW AND LEGAL LINGUISTICS IN A CONSTANT STATE OF TRANSITION - WAGNER, Anne; MATULEWSKA, Aleksandra (Comparative Legilinguistics, 2021)
Legal linguistics or jurilinguistics as it has been called recently, is a relatively new field of research. The first research into the field started with analysing the content of laws (the epistemic stage). Later on, lawyers started being interested in manners of communicating laws (the heuristic stage). This Special Issue of Comparative Legilinguistics contains two texts devoted to the development of legal linguistics, legal languages and legal translation and two papers on an institutional stratification of legal linguistics. It is a continuation of research published in the same journal (Special Issue no. 45 titled “The Evil Twins and Their Silent Otherness in Law and Legal Translation”) providing some insights into the problems of communication in legal settings.